Expression of Aldehyde Dehydrogenase 1A1 in Relapse-Associated Cells in Acute Myeloid Leukemia - Régis Costello; Garrett M. Dancik; Anaïs Dubiau; Lamia Madaci; Spiros Vlahopoulos (Cells, 2025)
In acute myeloid leukemia (AML) it is important to elucidate the biological events that lead from remission to relapse, which have a high probability of leading to an adverse disease outcome. The cancer stem cell marker aldehyde dehydrogenase 1 (ALDH1A1) is underexpressed in AML cells when compared to healthy cells, both at the RNA level and at the protein level, and at least in the former, both in the bone marrow and in peripheral blood. Nonetheless, ALDH1A1/ALDH1A2 activity increases in AML cells during disease relapse and is higher in adverse prognosis AML in comparison with favorable prognosis AML. Furthermore, especially in relapsed AML and in unfavorable AML, AML cells rich in ALDH1A1 can contain high levels of reactive oxygen species (ROS), in parallel with high ALDH1A1/2 activity. This metabolic feature is clearly incompatible with normal stem cells. The term “stem-like” therefore is useful to coin malignant cells with a variety of genetic makeups, metabolic programming and biomarkers that converge in the function of survival of clones sufficient to sustain, spread and re-establish neoplastic disease. Therefore, AML “stem-like” cells survive cancer treatment that eradicates other malignant cell clones. This fact differentiates AML “stem-like” cells from normal stem and progenitor cells that function in tissue regeneration as part of a distinct hierarchical order of cell phenotypes. The ODYSSEY clinical trial is a Phase I/II study designed to evaluate the safety, tolerability, pharmacokinetics, and pharmacodynamics of ABD-3001, a novel therapeutic agent, in patients with AML who have relapsed or are refractory to standard treatments. In this context, ABD-3001 is used as an inhibitor of cytosolic ALDH1 enzymes, such as ALDH1A1 and ALDH1A2.